Fractional growth model of abalone length - Susanto, Marliadi; Kilicman, Adem; Wahi, Nadihah (Elsevier, 2024)
This paper uses fractional growth model modified from McKendrick equation to describe the growth of abalone length. The fractional model is analyzed by generalized differential transform method to obtain Taylor’s series which is then used to predict the abalone length growth. The results are indicated by fractional order equal to 0.8. The results also show that by simulating the series with fractional order and integer order, the fractional model provides more robust results than the model with integer order.